Infectious Diseases Specialty Intervention Is Associated With Better Outcomes Among Privately Insured Individuals Receiving Outpatient Parenteral Antimicrobial Therapy. (21st September 2018) - Shah, Akshay; Petrak, Russell; Fliegelman, Robert; Shrestha, Nabin; Allison, Genève; Zurlo, John; Parker, Steven; Poretz, Donald; McKinsey, David; Dougherty, Mark; Martinelli, Lawrence; Mathur, Ajay; et al.
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) can be managed by specialists in infectious diseases (ID) or by other physicians. Better management of OPAT can reduce the likelihood of readmission or emergency department (ED) use. The relative success of ID specialists and other physicians in managing OPAT has received little study. Methods: We analyzed a national database of insurance claims for privately insured individuals under age 65, locating inpatient acute-care stays in 2013 and 2014 that were followed by OPAT. Through propensity scoring, patients who received outpatient ID intervention (ID-led OPAT) were matched 1-to-1 with those who did not (Other OPAT). We estimated regression models of hospital and ED admissions and of total healthcare payments over the first 30 days after discharge. Results: The final analytic sample of 8200 observations was well balanced on clinical and demographic characteristics. Soft-tissue infection and osteomyelitis were the most common infections in the index event, each affecting more than 40% of individuals. Relative to those with Other OPAT, people with ID-led OPAT had lower odds of an ED admission (odds ratio [OR] 0.449, 95% confidence interval [CI] 0.311–0.645) or hospitalization (OR 0.661, 95% CI 0.557–0.791) over 30 days, and they accumulated $1488 less in total healthcare payments (95% CI -2 688.56–-266.58). Conclusions: Among privately insured individuals below age 65, ID consultations during OPAT are associated with large and significant reductions in the rates of ED admission and hospital admission in the 30 days after index events, as well as lower total healthcare spending. Abstract : Infectious disease consultations during outpatient parenteral antimicrobial therapy are associated with large and significant reductions in the rates of emergency department admissions and hospital admissions in the 30 days after index events, and lower total healthcare spending.